Level of knowledge on Quranic symbols (Dabt al-Quran) in mushaf uthmani among the al-Quran teachers in Imtiaz, Terengganu - Wan Mohd Khairul Firdaus, Wan Khairuldin; Nurfaizah, Fauzi; Daud, Ismail (2017)
Quran is a revelation delivered to Prophet Muhammad s.a.w through angel of Jibril(Gabriel) as then subsequently written compilation into a manuscript. The Holy Quran covers many aspects of human life. Thus, the Quran should be taken care at its best, whether from the aspects of memorization, writing and also marking the diacritical points. Knowledge on putting the point, diagonal line and appropriate signs on mushaf al-Quran becomes obligatory for Muslims to help in reading, writing and understanding the Qur’an correctly. It also to avoid any errors and fraud against the Quran. However, there are still weaknesses on the knowledge of the symbols marking in the Quran among the Muslim community. Therefore, this study examines the relation of knowledge of quranic symbols in Uthmani Mushaf from the Islamic Scholar’s writing. This study objective to identify the level of knowledge among al-Quran teacher on quranic symbols in Mushaf Uthmani. This study uses quantitative methods, using the questionnaire as a tool of the study. The instrument has been tested on its validity and reliability to be used in questionnaire. Total number of respondents is a total of 127 people comprising al-Quran teachers in IMTIAZ, Terengganu. Data was analyzed using descriptive and inferential analyses through independent t-test. Overall, the results of this study found that those teachers have high level of knowledge about the symbols marking (dabt).Analysis of t-test also found there were no significant differences in min knowledge of the quranic symbols in Mushaf Uthmani based on race and gender among teachers of tasmi ‘al-Quran in Imtiaz, Yayasan Terengganu. Analysis of t-test also found there were no significant differences in min knowledge of the symbols marking (dabt) Uthmani Mushaf based on age and gender among al-Quran teachers in IMTIAZ.